2012
DOI: 10.2217/nnm.11.101
|View full text |Cite
|
Sign up to set email alerts
|

Ex Vivo Impact of Functionalized Carbon Nanotubes on Human Immune Cells

Abstract: Our results, on human cells ex vivo, confirmed previous studies demonstrating appropriately functionalized CNTs are nontoxic. The effects on cell functionality were significant for the monocytes and NK cells. These findings encourage the possible use of CNTs for biomedical applications either as carriers of therapeutic molecules or as immune modulator systems.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

5
75
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 77 publications
(80 citation statements)
references
References 59 publications
5
75
0
Order By: Relevance
“…Furthermore, the analysis of blood, including complete blood count and chemical profile, before the experiments and after 1 wk following ultrasonography, indicated that blood values were in normal range after MWCNT bladder injection (Table S1). Our data confirm previous studies showing that CNTs, appropriately functionalized, are nontoxic both in vitro toward different cell types and in vivo in mouse models (12,29,31,32). The main purpose of the overall study was to investigate functionalized MWCNTs as USCAs.…”
Section: Resultssupporting
confidence: 88%
See 2 more Smart Citations
“…Furthermore, the analysis of blood, including complete blood count and chemical profile, before the experiments and after 1 wk following ultrasonography, indicated that blood values were in normal range after MWCNT bladder injection (Table S1). Our data confirm previous studies showing that CNTs, appropriately functionalized, are nontoxic both in vitro toward different cell types and in vivo in mouse models (12,29,31,32). The main purpose of the overall study was to investigate functionalized MWCNTs as USCAs.…”
Section: Resultssupporting
confidence: 88%
“…S1) to render them biocompatible (12,15). These functionalized MWCNTs have a diameter of 20-30 nm and an average length of about 400 nm.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Pristine multi-walled carbon nanotubes (p-MWCNTs) were not able to cause secretion of cytokine in peripheral blood mononuclear cells (PBMCs), but could increase TLR agonist-induced cytokine secretion and PHAinduced T-cell cytokine release by PBMC. 3 In contrast to this, Delogu et al 9 demonstrated that f-MWCNTs had no cytotoxicity on human monocytes and NK cells. Similarly, Dumortier et al 12 found that the two types of f-MWCNTs neither decreased cellular vitality nor affected the functional activity of immunoregulatory cells.…”
mentioning
confidence: 94%
“…7 Due to their importance in the immune system, studies have reported the effects of CNTs on the functionality and viability of immune cells such as T and B lymphocytes, macrophages, dendritic cells, natural killer (NK) cells in vitro, focusing on toxicity, oxidative stress, cytokine induction, and inhibition of key functions such as phagocytosis. [8][9][10][11][12][13] Pescatori et al 8 showed that four types of functionalized multi-walled carbon nanotubes (f-MWCNTs) showed no cytotoxicity on Jurkat T and monocyte THP-1 cells, but three types of those f-MWCNTs activate the expression of pro-inflammatory genes in THP-1, whereas no significant activation was observed in T cells. Pristine multi-walled carbon nanotubes (p-MWCNTs) were not able to cause secretion of cytokine in peripheral blood mononuclear cells (PBMCs), but could increase TLR agonist-induced cytokine secretion and PHAinduced T-cell cytokine release by PBMC.…”
mentioning
confidence: 99%